Benefits of post-stress immunosuppression: a viewpoint from exercise immunology - Hiromi Yano; Michael J. Kremenik; Masataka Uchida; Eri Oyanagi (Japanese Society of Physical Fitness and Sports Medicine, 2018)
In understanding the relationship between exercise and immunity, the "open window theory" is a well-known theory stating that immediately after high intensity exercise, temporary immunosuppression occurs, which increases the risk of infections such as upper respiratory tract infections. Why does such a phenomenon occur? Does immunosuppression after severe exercise have physiological significance? In this paper, we propose a theory of super homeostasis. In other words, we verify that the open window theory is an important biological reaction when trying to understand the reason why we do exercise, more than it is the indispensable physiological response to the whole body.